Flow slip on a solid surface - Tan, Zi Hian (2015)
The no-slip boundary condition have been an assumption for many fluid mechanics problems. Though it has been challenged since the 1900’s, it was never proven until the development of precise measurement instruments. Today, it is well-known that fluid does slip at a solid interface, however the exact mechanism of slip is still unknown. To be able to engineer slip has great applications from microchannel flows, micro heat exchangers to reducing energy loss in chemical process plants. This report starts by introducing the phenomena of slip by reviewing experiments and studies done to validate the existence of slip. The experiments suggest that apparent slip is likely to occur rather than true slip and slip lengths can be greatly increased at the presence of nano-bubble layer. Current slip model are also reviewed to discuss on their limitations and inadequacy to provide a description on the slip mechanism. The physical nature of slip provides a clue to the mechanism of slip, however these relations are based on large scale observable phenomena. The present work attempts to derive a theoretical model and describe the mechanism of slip at the molecular level. There has been various Molecular Dynamics simulation done in the attempt to understand slip at the interface of fluid and solid. This work describes slip from a different approach, by taking reference from the theoretical studies of enzyme catalytic energetics. The model predicts qualitatively the critical point of slip; if the energy (shear rate) applied is inadequate slip does not occur, whereas if the applied shear rate is above a certain threshold slip occurs. The model is also able predict the dipole dependence of slip. This work suggest that slip is not only induced by shear rates. The dipole orientation of the adsorbed fluid molecules is a crucial part of the slip mechanism.